100 GHz free spectral range-tunable multi-wavelength fiber laser using single–multi–single mode fiber interferometer - Ahmad, Harith; Ooi, Shok Ing; Tiu, Zian Cheak (Springer, 2019)
Six single–multi–single (SMS) mode fiber-based Mach–Zehnder Interferometers (MZI) with different spooling radii are demonstrated as spatial mode filtering elements for multi-wavelength laser generation. Free spectral range (FSR) tuning of the multi-wavelength output generated is realized by alternating between the six MZIs, which have different macro-bending losses. Additional FSR tuning is also realized by changing the spooling radius of the two-mode step index fiber section within the MZI setups from 80 mm to 30 mm, giving an FSR tuning range of 0.89–0.99 nm. All generated multi-wavelength outputs show high stability over a test period of 100 min. The proposed multi-wavelength lasers are highly suitable for various microwave photonics applications the field of such as microwave signal source generation and microwave photonic filtering. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.